Systemowe podstawy pomocy osobom niepełnosprawnym - Baron-Wiaterek, Małgorzata (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: System basics assistance to disabled persons Issues relating to assistance to disabled persons settled in the basic legal acts: the Constitution and laws of the details. They identified the bodies of tasks to persons with reduced efficiency and basic tools. The effectiveness of the system to assist disabled persons in Poland is not only dependent on the improvement of legislation. Important is particularly appropriate action, forming a favourable mechanism for the disabled. Key words: assistance to disabled persons, legal acts, persons with reduced efficiency, basic tools of help